Mutation analysis in 24 French patients with glycogen storage disease type 1a. Issue 5 (May 1996) - Chevalier-Porst, F; Bozon, D; Bonardot, A M; Bruni, N; Mithieux, G; Mathieu, M; Maire, I
Abstract : Both alleles of 24 French glycogen storage disease type 1a patients were sequenced: 14 different mutations allowed the identification of complete genotypes for all the patients. Nine new gene alterations are reported. Five mutations, Q347X, R83C, D38V, G188R, and 158 del C, account for 75% of the mutated alleles. These data show that the molecular pathology of the glucose-6-phosphatase gene is heterogeneous in this population. Complete genotyping of the index case by systematic sequencing is necessary to allow prenatal diagnosis in chorionic villi for at risk couples.